2003
DOI: 10.1046/j.1365-2133.2003.05506.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative monitoring of warfarin in cutaneous surgery

Abstract: Our experience supports the continued and safe use of warfarin for a wide variety of cutaneous surgical procedures with a preoperative INR of < 3.5. We recommend a routine INR before the procedure, preferably within 24 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 18 publications
0
29
0
1
Order By: Relevance
“…2,14 A number of recent retrospective and prospective studies have shown that cutaneous surgery patients taking warfarin have an insignificant risk for severe bleeding in the postoperative period. [4][5][6]9 Alcalay 6 found no increase in postoperative bleeding in his study of 16 warfarin-treated patients compared to controls. Ah-Weng and colleagues 4 performed a retrospective review of 68 warfarin-treated patients that had perioperative INR levels checked before performing a variety of dermatologic procedures primarily consisting of punch and shave biopsies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…2,14 A number of recent retrospective and prospective studies have shown that cutaneous surgery patients taking warfarin have an insignificant risk for severe bleeding in the postoperative period. [4][5][6]9 Alcalay 6 found no increase in postoperative bleeding in his study of 16 warfarin-treated patients compared to controls. Ah-Weng and colleagues 4 performed a retrospective review of 68 warfarin-treated patients that had perioperative INR levels checked before performing a variety of dermatologic procedures primarily consisting of punch and shave biopsies.…”
Section: Discussionmentioning
confidence: 94%
“…[3][4][5][6][7][8][9][10] Many of these studies have been retrospective in nature, 4,5 and the few prospective studies currently in print enrolled fewer than 20 patients taking warfarin. [6][7][8][9] Many studies have also limited their focus on the incidence of severe postoperative bleeding complications, such as hematoma or uncontrollable intraoperative or postoperative bleeding.…”
mentioning
confidence: 99%
“…The INR should be at the lower end of therapeutic range, especially when several additional risk factors are present. A fixed INR recommendation cannot be made as the therapeutic range recommended for patients depends on the indication for anticoagulation 9,24 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years surgeons have been encouraged to continue warfarin and/or aspirin therapy before excision of skin tumours 4 -6,8 -14 , accepting an international normalized ratio (INR) of up to 3·5 9 . Stopping antithrombotic drugs risks life-threatening thromboembolic sequelae, even when medication is stopped only for a short period 1,15 -17 .…”
Section: Introductionmentioning
confidence: 99%
“…4,5,21,28 Evidence-based recommendations have been proposed to deal with this complicated countermeasure in some less invasive procedures with lower risk of bleeding, such as dental procedures or cataract operations. [1][2][3][6][7][8][9][10][11][12][13][14][15][16][17][18][19][21][22][23][24][25]29,30,[32][33][34][35][36][37][38] However, procedures without discontinuation of antithrombotic treatment have received little attention, 39 and the perioperative period in neurosurgical procedures has also been less well studied. 20,26,27,31,[40][41][42] The present clinical study retrospectively analyzed a series of transsphenoidal surgeries performed without discontinuation of antithrombotic therapy for comparison with the same number of transsphenoidal surgeries performed in the absence of antithrombotic therapy.…”
mentioning
confidence: 99%